Thermal measurements and inverse techniques - Orlande, Helcio R. B., 1965- (Boca Raton, FL . : CRC Press, 2011)
'The use of inverse problems constitutes a new research paradigm in which groups of theoretical, computational, and experimental researchers synergistically interact to better understand the physical phenomena being studied. This book presents a comprehensive research-based survey of modern inverse techniques and their applications to engineering heat transfer. Written by top-notch contributors, the text provides a concise, single-source reference on the mathematical modeling, measurements, and solution of inverse problems in heat transfer. It covers topics such as multiscale modeling, thermophysical properties, heat flux, and temperature measurements'--
Includes bibliographical references and index.
Keywords: Heat -- Transmission; Heat equation; Inverse problems (Differential equations).; Heat engineering